2021
DOI: 10.1111/1750-3841.15725
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between isolated sweetpotato starch properties and textural attributes of sweetpotato French fries

Abstract: Sweetpotato French fry (SPFF) textures have been associated with dry matter and starch contents, but these do not fully account for all textural differences. This study investigated the relationships between the physicochemical properties of sweetpotato starch and textural attributes of sweetpotato fries.Starches from 16 sweetpotato genotypes that varied in dry matter content were isolated and analyzed. The amylose content, pasting temperatures and viscosities, and textural properties of equilibrated starch ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The RVA viscosity values were significantly correlated with one another, which was consistent with the report by Allan et al. (2021).…”
Section: Resultssupporting
confidence: 92%
“…The RVA viscosity values were significantly correlated with one another, which was consistent with the report by Allan et al. (2021).…”
Section: Resultssupporting
confidence: 92%
“…Food science and breeding research has been conducted to develop processes and genotypes that are better suited for sweetpotato fries to improve textures and minimize acrylamide formation. It was identified that sweetpotato composition (e.g., starch, moisture, sugar contents), amylase activities, as well as starch viscoelastic, structural, and thermal properties all affect fry textures (Allan & Johanningsmeier, 2022; Allan et al., 2021; Sato et al., 2018). In addition, acrylamide formation can be minimized in sweetpotato fries by processing aids that interfere with the reaction or by removal of acrylamide precursors—reducing sugars and free asparagine (Truong et al., 2014).…”
Section: Health‐promoting Properties Of Sweetpotato Cultivars and Con...mentioning
confidence: 99%
“…Sensory traits can thus be quantitatively predicted based on instrumental measurements. [9][10][11][12] In addition, thresholds of texture attributes of RTB foods can be provided to breeders when textural data are juxtaposed with consumer surveys, thereby linking texture from raw product to controlled processing and to consumer preferences.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important to determine the texture of RTBs by instrumental protocols that can simulate sensory texture as much as possible, and to establish mathematical relationships between instrument and sensory perception. Sensory traits can thus be quantitatively predicted based on instrumental measurements 9‐12 . In addition, thresholds of texture attributes of RTB foods can be provided to breeders when textural data are juxtaposed with consumer surveys, thereby linking texture from raw product to controlled processing and to consumer preferences.…”
Section: Introductionmentioning
confidence: 99%